Eva´s Will: A Critical Review of Juan Martini`s Cine (Cinema) Trilogy - Rogna, Juan Ezequiel (2019)
In this study we will analyze the construction of Eva Perón as developed in Cine (Cinema), a triad of novels by Rosario-born writer Juan Martini (1944). We will base this study on the hypothesis that the changes experienced by Argentina over the last decade may have promoted the resurgence of Evita’s “political potentiality”, apparently “warded off” during the first years of this century (Saítta, 2002). In sync with this phenomenon and relying on literary fiction, Martini models an Eva in swift transition towards her political radicalization and mythical fate. Thus, her image has not ended up subsumed under the black anti-Peronist legend, the Justicialist hagiographic pitch, or the “artifact” forged by show business (Soria 2005); on the contrary it has come to embody the essence of the “Peronist myth” (Casullo 2008) out of the “hybridization” between the “logics of representation” of the State and the cultural industry that Peronism founded and which enabled Evita’s passage to the “legendary” dimension of “collective imagination” (Rosano 2006). We will additionally examine the subjective composition of Sivori, the film-maker who seeks to create an erratic film trilogy about Eva Perón, so as to contrast their respective wills and their dissimilar senses of transcendence.